Relationship between self-care level and risk of diabetic foot ulcers (DFU) in diabetes mellitus patients - Muhammad Basri; Mohamed Saifulaman Mohamed Said (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Diabetic foot ulcers are a serious complication that increases morbidity and amputation risk in patients with diabetes mellitus. Self-care is an important aspect of diabetes management that includes various health behaviours, such as diet, exercise, blood sugar monitoring, medication adherence and foot care. Purpose: To measures the relationship between the level of self-care of patients with diabetes mellitus (DM) and the risk of diabetic foot ulcers. Method: This study uses Analytical research methods using a Crossectional study approach. The sample size in this study used total sampling, from January to early March 2025, totalling 66 respondents. Data analysis to find the relationship between variables using non-parametric correlation test analysis, namely Spearman Correlation with a meaning level of 95% (0.05) because the data is ordinal scale. Results: This study found that based on statistical tests there was a correlation between the level of self-care and the risk of diabetic foot ulcers with a p value of 0.000 <0.05. Spearman's correlation value of 0.521 shows a positive correlation with a fairly strong correlation strength. Conclusion: The better the level of self-care of type 2 diabetes mellitus patients, the lower their risk of developing diabetic foot ulcers.